Research data for "Modelling Electric Field Control in a 4f Molecular Qudit with Hyperfine Coupling" - Nicholas Chilton (11394839) (2025)
All computational inputs and outputs describing the effect of electric fields on the [Tm(Ntt)2] molecule. This allows us to simulate the coherent spin dynamics of the electron and nuclear spins under the influence of static or pulsed electric fields.